PENGARUH AKUPRESUR TERHADAP PENURUNAN MUAL DAN MUNTAH PADA IBU HAMIL DI PRAKTEK MANDIRI BIDAN SIDOARJO: indonesia - Nanik Handayani; R.Khairiyatul Afiyah Khairiyatul (Program Studi S1 Kebidanan - Fakultas Sains dan Kesehatan Universitas PGRI Adi Buana Surabaya, 2019)
Nausea and vomiting are physiological things. This physiological condition will turn into pathology if not done with good care. Pregnant women often ignore complaints of nausea and vomiting because it is considered normal in early pregnancy. The purpose of this study was to determine the effectiveness of acupressure on reducing nausea and vomiting in pregnant women. The design of this study is Quasy-Experiment, a pre-post test control group design technique with a population of all pregnant women who experience nausea and vomiting. Sample size 22 of which 11 people were given intervention and 11 people as controls were taken by consecutive sampling technique. The data collection instrument was the PUQE score questionnaire. The results of the study in the intervention group before acupressure were an average of 8.00 and in the control group was 7.00. After acupressure, the intervention group had an average degree of nausea and vomiting of 5.00 and the control group was 6.63. There was a decrease in the intervention group that was 3, 00 and in the control group that was 0.36. The results of the statistical analysis of the Independent T-test ρ = 0.010 <α = 0.05, so that H0 is rejected means that acupressure is effective against decreasing nausea and vomiting. The more routine acupressure is done, the complaints of nausea and vomiting will decrease, so as to prevent complications in pregnant women